BEHAVIORAL DYNAMICS OF CAPTIVE BLUE BULLS (Boselaphus tragocamelus): IMPACTS OF SEASONALITY, GENDER, AND VISITOR INTERACTION ON WELFARE AND MANAGEMENT STRATEGIES - Hakim Bibi; Aim Iram Batool; Muhammad Fayyaz Ur Rehman; Misbah Sarwar; Saira Naz; Mohamed Mohany; Syed Sikandar Habib (Journal of Animal and Plant Sciences, 2025)
The Blue bull (Boselaphus tragocamelus), an endangered species in Pakistan, faces challenges in captivity due to limited research on behavioral dynamics and the impact of visitor interactions. This study examines seasonal and visitor-induced variations in the activity budgets of captive Blue bulls across four zoological facilities in Punjab, Pakistan, over a year. Detailed behavioral observations were conducted, capturing feeding, resting, social, and reproductive activities. Visitor density and behaviors were recorded to assess their influence on animal welfare. Results revealed distinct seasonal patterns, with increased feeding and drinking during autumn and heightened social and reproductive behaviors in winter. Visitor presence significantly altered behavior, with higher visitor numbers correlating with increased activity and social interactions but reduced resting times. These findings emphasize the critical need for season-specific enrichment and strategic visitor management to enhance animal welfare. This study provides actionable insights for optimizing zoo management practices and advancing conservation efforts for this endangered species.
Keywords: captive blue bull; behavioral ecology; seasonal behavior; animal welfare; Visitor effects